Laminated film structure having a barrier adhesive layer

By integrating a barrier adhesive layer between polymer film layers, the laminated film structures address the challenge of achieving gas and moisture barrier properties with reduced weight and complexity, enhancing flexibility and cost-effectiveness.

JP7604224B2Active Publication Date: 2024-12-23DOW GLOBAL TECHNOLOGIES LLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020516407
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-09-22
Filing Date
2018-07-17
Publication Date
2024-12-23
Estimated Expiration
2038-07-17

AI Technical Summary

Technical Problem

Existing laminated film structures for packaging face challenges in achieving gas and moisture barrier properties while minimizing weight, thickness, and number of layers, often leading to increased complexity and manufacturing costs.

Method used

Incorporating a barrier adhesive layer between polymer and/or metallized polymer film layers to reduce the weight, thickness, and number of layers while maintaining or improving barrier properties, using adhesives such as solvent-based, water-based, or solvent-free adhesives with isocyanate components.

Benefits of technology

The laminated film structures achieve comparable barrier performance with reduced weight, thickness, and number of layers, offering cost savings and simplified manufacturing processes, suitable for flexible packaging applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604224000008
    Figure 0007604224000008
  • Figure 0007604224000009
    Figure 0007604224000009
  • Figure 0007604224000010
    Figure 0007604224000010
Patent Text Reader

Abstract

A laminated film structure is disclosed that includes an adhesive layer with gas and moisture barrier properties. The disclosed laminated film structure includes films bonded together with an adhesive composition, which has barrier properties, such as controlling oxygen and / or water vapor transmission rates. The disclosed laminated film structure includes films made from polymers and / or metallized polymers, thereby reducing the weight, thickness, and / or number of film layers by using a barrier adhesive instead of a standard adhesive while still achieving similar barrier properties. A method for forming a laminated structure with desired barrier properties is also disclosed, which includes determining the desired barrier properties of the laminated structure, selecting a barrier adhesive, selecting two or more film layers, including at least a first film layer and a second film layer, applying the barrier adhesive to a surface of the first film layer, and contacting the surface of the second film layer with the barrier adhesive applied to the surface of the first film layer, thereby forming a laminated structure with desired barrier properties. [Selection diagram] None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Application No. 62 / 561,950, filed September 22, 2017.

[0002] The present disclosure relates to a laminated film structure comprising an adhesive layer having barrier properties. In particular, the disclosed laminated film structure comprises films bonded together by an adhesive layer, the adhesive layer having gas and / or moisture resistance, for example controlling oxygen and / or water vapor transmission rate. The disclosed laminated film structure comprises a film made of a polymer and / or a metallized polymer, thereby reducing the weight, thickness, and / or number of film layers by using a barrier adhesive composition instead of a standard adhesive composition while still achieving similar barrier properties. The present disclosure further relates to a method of forming a laminated structure with a barrier adhesive layer, which allows for a reduction in the weight, thickness, and / or number of film layers in a laminated structure relative to existing laminated structures while still achieving similar barrier properties. [Background technology]

[0003] Polymeric materials, and in particular films comprising polymeric materials, are widely used for packaging purposes. These polymeric materials find widespread application in the food and pharmaceutical industries, as well as in industrial and consumer applications. In these and other applications, exposing the packaged product to oxygen (and / or other gases) as well as moisture can be highly undesirable. This is especially the case when exposure to such gases and / or moisture would cause the packaged product to degrade over time. Unfortunately, many polymeric films are relatively permeable to gases and / or moisture in nature. One approach to enhancing the barrier properties investigated is to use multiple layers of polymeric materials and bond the layers together with an adhesive to form a laminate. In some cases, the polymeric material layers and / or adhesives are selected for their barrier properties.

[0004] In recent years, a high level of functionality has been required for multilayer films for long-term food storage, and gas barrier properties that prevent the intrusion of external oxygen to inhibit oxidation, carbon dioxide barrier properties, and barrier properties against various odorous components are currently required. When imparting a barrier function to a multilayer film, polyolefin films typically used as the inner layer (sealant side) have poor gas barrier properties, and it is difficult to impart a barrier function to these films by coating or vapor deposition. As a result, barrier functions are often imparted to various films used as the outer layer (including polyester resins such as polyethylene terephthalate (hereinafter abbreviated as "PET"), polyamide resins, and oriented polyolefin resins).

[0005] In some cases, the film layer itself is given a barrier function. When coatings are used to give these outer layer films a barrier function, one example of a widely used barrier coating material is vinylidene chloride, which exhibits excellent oxygen barrier properties and water vapor barrier properties. However, there are problems associated with the use of vinylidene chloride, including the production of dioxins when the material is incinerated during disposal. In addition, polyvinyl alcohol resins and ethylene-polyvinyl alcohol copolymers have also been used as barrier coating materials, but these materials exhibit good oxygen barrier properties under low humidity, but poor oxygen barrier properties under high humidity and are vulnerable to pinhole formation, thereby worsening the barrier performance and exhibiting poor boiling and retort resistance. On the other hand, films with a vapor-deposited layer of a metal such as aluminum provided as a gas barrier layer are opaque, which means that the contents inside cannot be seen and cannot be used in a microwave oven. In addition, films with a vapor-deposited layer of a metal oxide such as silica or alumina provided as a gas barrier layer are expensive, have poor flexibility, and result in large variations in gas barrier properties due to cracks and pinholes.

[0006] Furthermore, existing solutions for adding barrier functionality to laminate structures generally involve increasing the weight of the laminate structure by increasing the complexity of the structure (e.g., adding more layers with a particular barrier functionality) and / or increasing the thickness of the film layers to provide good barrier functionality. Increasing the complexity of these structures, either in the number of layers or layer thickness, increases manufacturing costs.

[0007] It therefore becomes desirable to have a laminate film structure that includes film layers made from polymers and / or metallized polymers, whereby the weight, thickness, and / or number of film layers is reduced compared to existing laminate structures while still achieving similar barrier properties.

[0008] Disclosed herein is a laminated film structure having a barrier adhesive layer. The disclosed laminated film structure is suitable for use in, for example, flexible packaging applications. The disclosed laminated film structure includes polymeric and / or metallized polymeric film layers bonded together by a barrier adhesive layer, whereby the weight, thickness, and / or number of film layers are reduced, replaced, or eliminated by the inclusion of a barrier adhesive layer in the laminated film structure. In some embodiments, the disclosed laminated film structure is recyclable. The disclosed laminated film structure can achieve the same or better desired barrier properties, such as gas and / or moisture permeability control, as current laminated film structures using standard adhesives. However, the disclosed laminated film structure is beneficial in that it reduces the cost and / or number of process steps required to manufacture current structures.

[0009] In some embodiments, the laminated film structure includes a film layer and a barrier adhesive layer disposed on a surface of the film layer. In some embodiments, the film layer is selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, polyamide, polystyrene, ethylene vinyl alcohol, polyvinyl chloride, cycloolefin copolymers, polyvinyl chloride, polymonochlorotrifluoroethylene, polyvinyl alcohol, citrine butadiene, and the like. In some embodiments, the barrier adhesive layer can include a solvent-based adhesive, a water-based adhesive, and / or a solventless adhesive. In some embodiments, the disclosed laminated film structure includes a film layer and a barrier adhesive layer disposed on a surface of the film layer, and the laminated film structure can have a viscosity of 20 ccO2 / m2 measured according to ASTM method D3985. 2 In some embodiments, the disclosed laminate film structure includes a film layer and a barrier adhesive layer disposed on a surface of the film layer, the laminate film structure having an oxygen transmission rate of 5 gmH2O / m2 or less as measured according to ASTM method F1249. 2 / day or less water vapor transmission rate.

[0010] A method for forming a laminated structure having a desired barrier performance is also disclosed. In some embodiments, the method includes determining the desired barrier performance of the laminated structure, selecting a barrier adhesive, selecting two or more film layers including at least a first film layer and a second film layer, applying the barrier adhesive on a surface of the first film layer, and contacting a surface of the second film layer with the barrier adhesive applied on the surface of the first film layer, thereby forming a laminated structure having the desired barrier performance.

[0011] Also disclosed are articles comprising the disclosed laminate film structures. In some embodiments, the disclosed articles include, for example, flexible packaging, pouches, stand-up pouches, bags, and the like. [Brief description of the drawings]

[0012] Please refer to the attached drawings: [Figure 1] FIG. 1 is a schematic diagram of a current BOPP / metallized-BOPP laminate film structure and a new BOPP / BOPP laminate film structure using a barrier adhesive, where the current film structure and the new film structure have similar barrier properties. [Diagram 2] FIG. 1 is a schematic diagram of a current BOPP / / metallized-BOPP / / PE laminate film structure and a new BOPP / / PE laminate film structure with a barrier adhesive, where the current film structure and the new film structure have similar barrier properties. [Diagram 3] FIG. 1 is a schematic diagram of a current BOPP / / PE laminate film structure and a new BOPP / / PE laminate film structure with a barrier adhesive, where the current film structure and the new film structure have similar barrier properties. [Figure 4] FIG. 1 is a schematic diagram of a current BOPP / / BOPP laminate film structure and a new BOPP / BOPP laminate film structure using a barrier adhesive, where the current film structure and the new film structure have similar barrier properties. [Diagram 5] FIG. 1 is a schematic diagram of a current PET / / PE laminate film structure and a new PET / / PE laminate film structure using a barrier adhesive, where the current film structure and the new film structure have similar barrier properties. [Figure 6] FIG. 1 is a schematic diagram of a current PET / / PE / EVOH / PE laminate film structure and a new PET / / PE / EVOH / PE laminate film structure using a barrier adhesive. The current film structure and the new film structure have similar barrier properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In some embodiments, the disclosed laminate film structure includes a film layer made of a polymer or a metallized polymer and a barrier adhesive layer disposed on a surface of the film layer. In some embodiments, a laminate film structure is disclosed that includes a first film layer, a second film layer, and a barrier adhesive layer disposed intermediate the first and second film layers.

[0014] In some embodiments, the film layer is selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, nylon, polystyrene, and polyvinyl chloride. In some embodiments, the barrier adhesive layer comprises a solvent-based adhesive, a water-based adhesive, and / or a solventless adhesive.

[0015] In some embodiments, the laminate film structure has a viscosity of 20 ccO2 / m2 measured according to ASTM method D3985. 2 / day or less. In some embodiments, the laminate film structure has an oxygen transmission rate of 5 gmH2O / m 2 / day or less water vapor transmission rate.

[0016] In some embodiments, the barrier adhesive comprises an isocyanate component and an isocyanate-reactive component. In some embodiments, the isocyanate component comprises a single polyisocyanate. In some embodiments, the polyisocyanate is an aliphatic polyisocyanate. In some embodiments, the polyisocyanate is selected from polymeric hexamethylene diisocyanate (HDI trimer isocyanurate), methylene diphenyl diisocyanate, dicyclohexylmethane 4,4'-diisocyanate, and toluene diisocyanate. In some embodiments, the isocyanate-reactive component comprises a hydroxyl-terminated polyester incorporated as a substantially miscible solid in a carrier solvent, the polyester being formed from a single linear aliphatic diol having terminal hydroxyl groups and 2-10 carbon atoms, and a linear dicarboxylic acid, the polyester having a number average molecular weight of 300-5,000, being solid at 25°C, and having a melting point of 80°C or less. In some embodiments, the carrier solvent is selected from ethyl acetate, methyl ethyl ketone, dioxolane, acetone, and combinations thereof. In some embodiments, the hydroxyl terminated polyester is formed from a C3-C6 diol and a dicarboxylic acid selected from adipic acid, azelaic acid, sebacic acid, and combinations thereof. In some embodiments, the isocyanate-reactive component further comprises an acrylate viscosity modifier. In some embodiments, the weight ratio of isocyanate component to isocyanate-reactive component in the barrier adhesive is 1:1 to 2:1.

[0017] In some embodiments, another film layer made of a polymer or metallized polymer contacts the film layer having a barrier adhesive layer disposed thereon, thereby creating a laminated film structure. The laminated film may be multi-layer or mono-layer. In each embodiment of the present disclosure, the disclosed laminated film structure reduces the weight, thickness, and / or number of film layers compared to current laminated structures while still achieving similar barrier properties. By using a barrier adhesive layer instead of a standard adhesive, the permeability of oxygen and / or moisture through the laminated structure is reduced. To better understand the potential applications of the barrier adhesive, the permeability of the barrier adhesive being used is evaluated by preparing samples that are tested to generate performance data. The permeability of the barrier adhesive is derived from the data, and a model is created that allows the design of various film structures to take advantage of potential cost savings, layer reduction, construction simplification, or sustainability by downgauging with a barrier adhesive instead of a standard adhesive.

[0018] The barrier performance of the barrier adhesive must then first be quantified before a model can be produced that can be used to predict laminate performance with and without the barrier adhesive. To generate data to support the model, several specimens are prepared and tested using a barrier adhesive composed of 25-35 wt% crystalline polyester resin, 0.25% defoamer 7R10 (an acrylic copolymer with ethyl acetate), and 64.75 wt% urethane grade ethyl acetate. The polyester is cured with an aliphatic isocyanate co-reactant.

[0019] The samples are processed into laminates as shown in Tables 1 and 2 below using a LABO COMBI™ 400 Laminator or a SUPER COMBI™ 3000 Laminator depending on the sample. The barrier adhesive is coated onto the film via a gravure cylinder. In Tables 1 and 2, the film coated is the first film listed for the particular construction. For the gravure cylinder, a 130 quad with 15 BCM is used. The adhesive is applied at approximately 3 g / m2. 2 The film is then passed through a three-zone oven with the first zone set at 90°C, the second zone at 100°C, and the third zone at 110°C when run on a LABO COMBI™ 400 laminator. The film is then passed through a two-zone oven with the first zone set at 80°C and the second zone at 100°C when run on a SUPER COMBI™ 3000 laminator. The coated film is then nipped to another film under a heated steel roll with a temperature of 90°C, and the nip pressure is set at 40 psi. The laminated structure passes through a final chill roll with a temperature of 17°C. The laminate is then placed in a temperature-controlled room to cure for 7 days at 23°C and 50% relative humidity.

[0020] The oxygen transmission rate of the sample laminate structure is tested according to the method outlined in ASTM Method D3985 (Standard Test Method for Oxygen Gas Transmission Rate through Plastic Films and Sheets Using a Coulometric Sensor). The water vapor transmission rate of the laminate structure is tested according to the method outlined in ASTM Method F1249.

[0021] From the permeability data of the sample laminate structure, the permeability of the barrier adhesive itself can be determined. The transmission rate ("TR") of vapor through a solid barrier can be described as a function of the permeability ("P") (the solubility of the vapor in the solid and the diffusion of the vapor as it is transported through the medium) and the path length or thickness ("L") of the solid material. For a multi-layer solid with materials of different thicknesses (L1, L2, etc.) and permeabilities (P1, P2, etc.), the total water vapor transmission rate TR 合計can be explained as follows:

number

[0022] TR for oxygen and water vapor 合計 The experimental data for was used with a series of experimentally produced laminated multi-layer structures to determine the average permeability as a function of thickness for the disclosed and comparative adhesive compositions, as detailed in Tables 1 and 2. [Table 1] [Table 2]

[0023] From the analyzed samples, as shown in Tables 1 and 2, the barrier adhesive had an oxygen concentration of 1.37ccO2 / m 2 / day oxygen transmission rate and 1.20 gmH2O / m 2 It is estimated that the adhesive has a water vapor transmission rate of 100 / day. This particular barrier adhesive is used in the models discussed herein to predict the performance of various laminate structures. However, other barrier adhesives can be used in accordance with the present disclosure after determining the oxygen and water vapor transmission rates.

[0024] The estimated oxygen and water vapor transmission rates of the barrier adhesives, along with known transmission rates for various plastic films shown in Tables 3 and 4, are used to model laminate film structures, including those represented diagrammatically in Figures 1-6. [Table 3] [Table 4]

[0025] For example, Figure 1 shows a schematic diagram of the current BOPP / met-BOPP laminate film structure and the new BOPP / BOPP laminate film structure with a barrier adhesive. The current BOPP / met-BOPP laminate film structure includes a 20 μm BOPP film laminated to a 20 μm metallized BOPP film using a standard adhesive, and has an average air permeability of 14.9 ccO2 / m 2 The new BOPP / BOPP laminated film structure with barrier adhesive, which includes a 20 μm BOPP film laminated to another 20 μm BOPP film with a barrier adhesive, has a calculated oxygen transmission rate of 13.6 ccO2 / m 2 / day. As is evident from Figure 1 and the calculated oxygen transmission rates, the metallized BOPP layer can be completely removed from the laminate structure while still achieving the same oxygen barrier performance. The current film and the new film are suitable for the same end use (e.g., packaging applications).

[0026] Figure 2 shows a schematic diagram of the current BOPP / / met-BOPP / / PE laminate film structure and the new BOPP / / PE laminate film structure with a barrier adhesive. The current BOPP / / met-BOPP / / PE laminate film structure includes a 20 μm BOPP film laminated to a 20 μm metallized BOPP film with a standard adhesive and a 50 μm PE film laminated to the metallized BOPP film with an additional standard adhesive. The current BOPP / / met-BOPP / / PE laminate film structure has an average air permeability of 14.8 ccO2 / m 2 The new BOPP / PE laminated film construction with barrier adhesive contains a 20μm BOPP film laminated to a 50μm PE film using a barrier adhesive and has a calculated oxygen transmission rate of 13.6ccO2 / m 2 1 / day. As is evident from Figure 2 and the calculated oxygen transmission rates, the metallized BOPP layer can be completely removed from the laminate structure while still achieving the same oxygen barrier performance. The current film and the new film are suitable for the same end use (e.g., packaging applications).

[0027] Figure 3 shows a schematic diagram of the current BOPP / PE laminate film structure and the new BOPP / PE laminate film structure with barrier adhesive. The current BOPP / PE laminate film structure includes a 20 μm BOPP film laminated to a 70 μm PE film with a standard adhesive, and has a barrier adhesive of 2.80 gmH2O / m 2 The new BOPP / PE laminate film construction with barrier adhesive, which includes a 20 μm BOPP film laminated to a 40 μm PE film using a barrier adhesive, has a calculated water vapor transmission rate of 2.82 gmH2O / m 2 3 and the calculated water vapor transmission rate of 1000 / day. As is evident from Figure 3 and the calculated water vapor transmission rates, the thickness of the PE film can be significantly reduced while achieving the same moisture barrier performance. The current film and the new film are suitable for the same end use (e.g., packaging applications).

[0028] Figure 4 shows a schematic diagram of the current BOPP / / BOPP laminate film structure and the new BOPP / / BOPP laminate film structure with a barrier adhesive. The current BOPP / / BOPP laminate film structure includes a 20 μm BOPP film laminated to a 20 μm BOPP film using a standard adhesive, with a barrier adhesive of 3.15 gmH2O / m 2 The new BOPP / / BOPP laminate film construction with barrier adhesive, which includes a 15 μm BOPP film laminated to a 15 μm BOPP film using a barrier adhesive, has a calculated water vapor transmission rate of 3.12 gmH2O / m 2 3. The new film has a calculated water vapor transmission rate of 1000 / day. As is evident from Figure 4 and the calculated water vapor transmission rates, the thickness of the BOPP film can be significantly reduced while achieving the same moisture barrier performance. The current film and the new film are suitable for the same end use (e.g., packaging applications).

[0029] Figure 5 shows a schematic diagram of the current PET / PE laminate film structure and the new PET / PE laminate film structure with a barrier adhesive. The current PET / PE laminate film structure includes a 12 μm PET film laminated to an 80 μm PE film using a standard adhesive, with a barrier adhesive of 4 gmH2O / m 2 The new PET / PE laminate film construction with barrier adhesive contains a 12 μm PET film laminated to a 50 μm PE film using a barrier adhesive, and has a calculated water vapor transmission rate of 4 gmH2O / m 2 5 and the calculated water vapor transmission rate of 1000 / day. As is evident from Figure 5 and the calculated water vapor transmission rates, the thickness of the PE film can be significantly reduced while achieving the same moisture barrier performance. The current film and the new film are suitable for the same end use (e.g., packaging applications).

[0030] Figure 6 shows a schematic diagram of the current PET / / PE / EVOH / PE laminate film structure and the new PET / / PE / EVOH / PE laminate film structure with a barrier adhesive. The current PET / / PE / EVOH / PE laminate film structure includes a 12 μm PET film laminated to a 60 μm EVOH film using a standard adhesive. The current PET / / PE / EVOH / PE laminate film structure has a 1.60 ccO2 / m 2 The new PET / PE / EVOH / PE laminate film structure with barrier adhesive contains a 12 μm PET film laminated to a 50 μm EVOH film using a barrier adhesive, and has a calculated oxygen transmission rate of 1.63 ccO2 / m 2 / day. As is evident from Figure 6 and the calculated oxygen transmission rates, the EVOH film can be significantly lowered while still achieving the same oxygen barrier performance. The current film and the new film are suitable for the same end use (e.g., packaging applications).

[0031] The measured or calculated performance OTR and WVTR for each laminate film structure in Figures 1-6 are summarized in Tables 5 and 6 below. The first row under each figure row below represents the measured properties and the second row under each figure row represents the calculated properties. For example, using the rows in Figure 1, the row for the 20μ BOPP / 20μ MET BOPP structure identifies the measured properties and the row for the 20μ BOPP / 20μ BOPP structure represents the calculated properties. [Table 5] [Table 6]

[0032] The structures tested and modeled, i.e., those shown in Figures 1-6, are not the only film structures and polymers that can be modified or replaced in accordance with this disclosure. The barrier performance of the barrier adhesive may be suitable for downgauging or replacing other materials in the laminate structure, such as nylon, oriented polystyrene, and / or polyvinyl dichloride ("PVDC"), among other materials. By determining the desired barrier performance of the laminate film structure, selecting a barrier adhesive with known / determinable permeability, and identifying the permeability of the films used in the laminate film structure, a film structure can be prepared that achieves similar barrier performance to existing films while reducing the number of films in the structure and / or the thickness of the films in the structure.

[0033] Also disclosed are articles comprising the disclosed laminated film structures. In some embodiments, the articles include flexible packaging and stand-up pouches.

[0034] In addition to the embodiments described above, many embodiments of specific combinations are within the scope of this disclosure, some of which are described below: Embodiment 1. A laminated film structure suitable for use in flexible packaging, comprising: A film layer; a barrier adhesive layer disposed on a surface of the film layer; The laminated film structure has a thermal conductivity of 20ccO2 / m2 measured according to ASTM method D3985. 2 Laminated film structure with oxygen permeability of less than 1000ppm / day. Embodiment 2. A laminated film structure suitable for use in flexible packaging, comprising: A film layer; a barrier adhesive layer disposed on a surface of the film layer; Laminated film structure has a thermal conductivity of 5 gmH2O / m2 measured according to ASTM method F1249 2 Laminated film structure with a water vapor permeability rate of less than 100 / day. Embodiment 3. A laminated film structure suitable for use in flexible packaging, comprising: a first film layer; a second film layer; and a barrier adhesive layer disposed intermediate the first film layer and the second film layer; The laminated film structure has a thermal conductivity of 20ccO2 / m2 measured according to ASTM method D3985. 2 Laminated film structure with oxygen permeability of less than 1000ppm / day. Embodiment 4. A laminated film structure suitable for use in flexible packaging, comprising: a first film layer; a second film layer; and a barrier adhesive layer disposed intermediate the first film layer and the second film layer; Laminated film structure has a thermal conductivity of 205 gmH2O / m2 measured according to ASTM method D3985 2 Laminated film structure with oxygen permeability of less than 1000ppm / day. Embodiment 5. The laminate film structure of any of the preceding or subsequent embodiments, wherein the barrier adhesive layer comprises a solvent-based adhesive. Embodiment 6. The laminate film structure of any of the preceding or subsequent embodiments, wherein the barrier adhesive layer comprises a water-based adhesive. Embodiment 7. The laminate film structure of any of the preceding or subsequent embodiments, wherein the barrier adhesive layer comprises a solventless adhesive. Embodiment 8. The laminate film structure of any preceding or subsequent embodiment, wherein the first film layer comprises a polymer selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, nylon, polystyrene, and polyvinyl chloride. Embodiment 9. The laminate film structure of any preceding or subsequent embodiment, wherein the second film layer comprises a polymer selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, nylon, polystyrene, and polyvinyl chloride. Embodiment 10. The laminate film structure of any preceding or subsequent embodiment, wherein the first film layer and the second film layer comprise the same polymer. Embodiment 11. The laminate film structure of any of the preceding or subsequent embodiments, wherein the laminate structure does not include a metallized film layer. Embodiment 12. The laminate film structure of any preceding or subsequent embodiment, wherein the first film layer has a thickness of 25 μm or less. Embodiment 13. The laminate film structure of any preceding or subsequent embodiment, wherein the first film layer has a thickness of 20 μm or less. Embodiment 14. The laminate film structure of any preceding or subsequent embodiment, wherein the first film layer has a thickness of 15 μm or less. Embodiment 15. The laminate film structure of any preceding or subsequent embodiment, wherein the second film layer has a thickness of 25 μm or less. Embodiment 16. The laminate film structure of any preceding or subsequent embodiment, wherein the second film layer has a thickness of 20 μm or less. Embodiment 17. The laminate film structure of any preceding or subsequent embodiment, wherein the second film layer has a thickness of 15 μm or less. Embodiment 18. The barrier adhesive layer comprises: an isocyanate component including a single type of polyisocyanate; and an isocyanate-reactive component comprising a hydroxyl-terminated polyester incorporated as a substantially miscible solid in a carrier solvent, wherein the polyester is formed from a single type of linear, aliphatic diol having terminal hydroxyl groups and 2 to 10 carbon atoms, and a linear dicarboxylic acid, wherein the polyester has a number average molecular weight of 300 to 5,000, is a solid at 25° C., and has a melting point of 80° C. or less. Embodiment 19. An article comprising the laminated film structure of any of the preceding or following embodiments. Embodiment 20. The article of any preceding or subsequent embodiment, wherein the article is a flexible package. Embodiment 21. The article of any preceding or subsequent embodiment, wherein the article is a stand-up pouch. Embodiment 22. A method for forming a laminated structure having desired barrier properties, comprising: Determining the desired barrier performance of the laminate structure; Selecting a barrier adhesive; selecting two or more film layers including at least a first film layer and a second film layer; applying a barrier adhesive onto a surface of a first film layer; and contacting a surface of the second film layer with a barrier adhesive applied on the surface of the first film layer, thereby forming a laminate structure having desired barrier performance. Embodiment 23. The method of any preceding or subsequent embodiment, further comprising selecting a third film layer and contacting a surface of the third film layer with a surface of the first film layer or the second film layer. Embodiment 24. The method of any preceding or subsequent embodiment, wherein the laminate film structure has a thickness less than the thickness of an existing laminate structure having a comparable desired barrier performance. Embodiment 25. The desired barrier performance is 20 ccO2 / m2 measured according to ASTM method D3985. 2 13. The method of any preceding or subsequent embodiment, wherein the oxygen permeability is equal to or less than 1 / 2 s. Embodiment 26. The desired barrier performance is 5 gmH2O / m2 measured according to ASTM method F1249. 2 The method of any preceding or subsequent embodiment, wherein the water vapor transmission rate is equal to or less than 1 / 2 s.

Claims

1. 1. A laminated film structure suitable for use in flexible packaging, the laminated film structure not including a metallized film layer, comprising: a first film layer; a barrier adhesive layer disposed on a surface of the first film layer; The laminated film structure has a viscosity of 20 ccO measured at 85% relative humidity (RH) according to ASTM method D3985. 2 / m 2 / day or less of oxygen transmission rate, The barrier adhesive layer comprises: an isocyanate component including a single type of polyisocyanate; an isocyanate-reactive component comprising a hydroxyl-terminated polyester incorporated as a substantially miscible solid in a carrier solvent, said polyester being formed from a single linear aliphatic diol having terminal hydroxyl groups and 2 to 10 carbon atoms, and a linear dicarboxylic acid, said polyester having a number average molecular weight of 300 to 5,000, being a solid at 25° C., and having a melting point of 80° C. or less; the weight ratio of said isocyanate component to said isocyanate-reactive component is from 1:1 to 2:1; A laminated film structure, wherein the first film layer has a thickness of 20 μm or less.

2. 10. The laminated film structure of claim 1, wherein the first film layer comprises a polymer selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, nylon, polystyrene, and polyvinyl chloride.

3. 10. The laminated film structure of claim 1, further comprising a second film layer, said second film layer comprising a polymer selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, nylon, polystyrene, and polyvinyl chloride, and said barrier adhesive layer disposed intermediate said first film layer and said second film layer.

4. An article comprising the laminated film structure of claim 1.

5. A method for forming the laminated film structure of any one of claims 1 to 3, comprising the steps of: determining a desired barrier performance of the laminated film structure; Selecting a barrier adhesive; selecting two or more film layers including at least a first film layer and a second film layer; applying the barrier adhesive onto a surface of the first film layer; and contacting a surface of the second film layer with the barrier adhesive applied on the surface of the first film layer, thereby forming the laminated film structure having desired barrier performance.

6. 6. The method of claim 5, wherein the laminated film structure has a thickness less than the thickness of an existing laminated film structure having comparable desired barrier performance.

7. The desired barrier performance is 20 ccO measured at 85% relative humidity (RH) according to ASTM method D3985. 2 / m 2 6. The method of claim 5, wherein the oxygen transmission rate is equal to or less than 100% by weight per day.

8. The desired barrier performance is 5 gmH 2 O / m 2 6. The method of claim 5, wherein the water vapor transmission rate is less than or equal to 100 / day.

Citation Information

Patent Citations

  • Lamination of polymer film

    JP1999148066A

  • Method of making laminates with reduced oxygen permeability

    JP2016537216A

  • Oxygen-barrier film and adhesive

    WO2011162160A1